Determining the knowledge and experience of the performance management and development system amongst nurses at the district hospital in Tshwane - Nhede, Norman Tafirenyika (University of Pretoria, 2023)
Dissertation (MAdmin (Public Management and Policy))--University of Pretoria, 2022.